The housing market, household portfolios and the German consumer - Felix Geiger; John Muellbauer; Manuel Rupprecht (European Central Bank (ECB), 2016)
House price booms in Anglo-Saxon economies and their collapse were an important part of the financial accelerator via consumption, construction and the banking system. This paper examines links for Germany between household portfolios, income and consumption in a six-equation system, for 1980-2012 data, for consumption, house prices, consumer credit, housing loans, liquid assets and permanent income with latent variables representing the shifts in the availability of the two types of credit. We find evidence of well specified consumption and house price functions and that Germany differs greatly from the Anglo-Saxon economies: rising house prices do not translate into higher consumer spending. This suggests that the transmission of monetary policy via asset prices, in particular house prices, on consumption is likely to be less effective, and any financial accelerator weaker, in Germany than in the US or the UK. There is little evidence of overvaluation of German house prices by 2012.
Keywords: E21; E27; E44; E51; E58; 330; consumption; credit conditions; credit market liberalization; household debt; housing collateral; monetary transmission